Exploration of the nitrogen heterocyclic periphery around the core of the advanced FFA1 agonist fasiglifam (TAK‐875). Issue 4 (3rd December 2020) - Lukin, Alexey; Bakholdina, Anna; Zhurilo, Nikolay; Onopchenko, Oleksandra; Zhuravel, Elena; Zozulya, Sergey; Gureev, Maxim; Safrygin, Alexander; Krasavin, Mikhail
Abstract: Three types of heterocyclic moieties—piperidines fused to a heteroaromatic moiety—were explored as potential periphery motifs for the pharmacophoric core of fasiglifam (TAK‐875), with fasiglifam being the most advanced agonist of free fatty acid receptor 1, a promising target for therapeutic intervention in type 2 diabetes. Several observed structure–activity relationship trends were corroborated by in silico docking results. Balanced selection based on potency and Caco‐2 permeability advanced six compounds to cellular efficacy tests (glucose‐stimulated insulin secretion in rat insulinoma INS1E cells). This led to the nomination of compound 16a (LK1408, 3‐[4‐({4‐[(3‐{[(2‐fluorobenzyl)oxy]methyl}‐1‐methyl‐1, 4, 6, 7‐tetrahydro‐5 H ‐pyrazolo[4, 3‐ c ]pyridin‐5‐yl)methyl]benzyl}oxy)phenyl]propanoic acid hydrochloride) as the lead for further development. Abstract : Three types of heterocyclic moieties were explored as potential periphery motifs for the pharmacophoric core of fasiglifam (TAK‐875). Six compounds were tested for their efficacy to affect glucose‐stimulated insulin secretion in rat insulinoma INS1E cells, leading to the identification of compound 16a (LK1408) as a lead for further development as an anti‐type 2 diabetes agent.